Production of Aflatoxin M in a Liquid Medium - Pai, M. Ramachandra (1975)
Aspergillus flavus NRRL 3251 grown on modified yeast extract-sucrose medium produced 1 mg of aflatoxin M(1) per 100 ml of medium.